The Association Between Lung Carcinoma and Tuberculosis - Cukic, Vesna (Med Arch, 2017)
INTRODUCTION: The association between lung tuberculosis and lung carcinoma is still controversial. OBJECTIVE: to describe the characteristics of patients with associated lung tuberculosis (TB) and lung carcinoma (LC) in patients treated in Clinic for pulmonary diseases and TB “Podhrastovi”. MATERIAL AND METHODS: This is the retrospective study of patients with LC associated with TB treated in Clinic for pulmonary diseases and TB “Podhrastovi” in five-year period -from 2012 to 2016. We analyzed sex and age of patients, whether TB preceded LC or LC preceded TB, a time period between the developments of these two diseases, activity of TB, the histopathological type of LC, localization of LC in lungs (bronchial, peripheral, cavern) according to histopathological type. RESULTS: In this period there were 2608 patients treated for LC. Among them there were 34 patients with diagnosed TB or 1.3%. All of them were smokers. No one had active TB. TB was the first diagnosis in all these patients. Each patient was previously treated for TB in hospital and had regular anti TB treatment. TB preceded LC in median time of 5 years (interquartile range 2 to 25 years). In 21 cases it was carcinoma of the drainage bronchus, in 11 cases it was peripheral lung carcinoma and 2 cases it was cavern carcinoma. CONLUSION: patients with cured pulmonary tuberculosis represent a group at risk for developing lung carcinoma. Changes in the bronchial and alveolar mucosa which tuberculosis leaves behind in the lungs must be taken as a possible place of later malignant alteration. Patients with any form of pulmonary tuberculosis have to be controlled continuously.